“Explaining Is Where We All Get Into Trouble”: Anti-Philosophical Philosophies in Richard Ford’s Bascombe Novels - Nicholas Manning (Transatlantica)
“Explaining is where we all get into trouble,” affirms Richard Ford’s anti-hero Frank Bascombe in The Sportswriter. Frank spends however a great deal of the novel explaining why explanation must be avoided, and why life must be not interpreted, but rather lived. This position may be compared to Nick Shay’s misological efforts, in Don DeLillo’s Underworld, to preserve a “wordless shock” before the world, or the renouncement of the search for meaning in Philip Roth’s American Pastoral (“He had learned the worst lesson that life can teach—that it makes no sense”). Such explicit protests against self-reflection may initially appear symptomatic of an anti-intellectual impetus within a society which views philosophy as a threatening limitation of the free American self. As challenges to a reductive, rationalizing and explicative logos, such novelistic discourses of resistance against the philosophical are highly self-critical, self-reflexive, and metatextual. They thus represent a solipsistic philosophy, with a history arguably as long as philosophy itself, which this article considers in specific reference to the fiction of Richard Ford, especially his 1986 novel The Sportswriter. Far from proposing the United States as an anti-philosophical culture, these discourses, as fictional incarnations of an ironic Socratic archetype, rather explore ways in which modes of reticence against philosophy, construed at once as an institution, mode of discourse, and epistemological method, are themselves explicitly philosophical positionings.